2018
DOI: 10.1007/s10461-018-2139-9
|View full text |Cite
|
Sign up to set email alerts
|

Poppers and PrEP: Use of Pre-exposure Prophylaxis Among Men Who Have Sex with Men Who Use Inhaled Nitrites

Abstract: Men who have sex with men (MSM) commonly use inhaled nitrites, or poppers, though their use is a risk factor HIV seroconversion. Pre-exposure prophylaxis, or PrEP, is effective for HIV prevention, but is not widely used, and little is known regarding PrEP use and acceptability among MSM who use inhaled nitrites. We surveyed 580 MSM in Paris, France in 2016 about popper use, sexual behaviors including condomless anal intercourse (CAI), serosorting, and sexual positioning, PrEP use, PrEP candidacy, and interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…A behavior common among MSM relates to the significant proportion of these individuals who use inhaled nitrites, or poppers, to enhance sexual intercourse. A survey was conducted in 2016 in 580 MSM living in Paris (France) regarding the use of poppers, condomless sexual anal intercourse, serosorting, sexual positioning, use of PrEP, PrEP candidacy and even interest in different possibilities for PrEP delivery ( 62 ). The study showed that popper users were more likely to consider themselves suitable candidates for PrEP, while showing that they were most probably not current or past users of PrEP ( 62 ).…”
Section: Implementation and Access To Prep As Part Of A Combination Prevention Strategy For Msm In Europementioning
confidence: 99%
See 2 more Smart Citations
“…A behavior common among MSM relates to the significant proportion of these individuals who use inhaled nitrites, or poppers, to enhance sexual intercourse. A survey was conducted in 2016 in 580 MSM living in Paris (France) regarding the use of poppers, condomless sexual anal intercourse, serosorting, sexual positioning, use of PrEP, PrEP candidacy and even interest in different possibilities for PrEP delivery ( 62 ). The study showed that popper users were more likely to consider themselves suitable candidates for PrEP, while showing that they were most probably not current or past users of PrEP ( 62 ).…”
Section: Implementation and Access To Prep As Part Of A Combination Prevention Strategy For Msm In Europementioning
confidence: 99%
“…A survey was conducted in 2016 in 580 MSM living in Paris (France) regarding the use of poppers, condomless sexual anal intercourse, serosorting, sexual positioning, use of PrEP, PrEP candidacy and even interest in different possibilities for PrEP delivery ( 62 ). The study showed that popper users were more likely to consider themselves suitable candidates for PrEP, while showing that they were most probably not current or past users of PrEP ( 62 ). Explanations for the belief that these individuals would be suitable candidates and actively considered PrEP were related to increased serosorting and condomless anal sexual intercourse reported by these participants ( 62 ).…”
Section: Implementation and Access To Prep As Part Of A Combination Prevention Strategy For Msm In Europementioning
confidence: 99%
See 1 more Smart Citation
“…Poppers were originally intended to aid in the treatment of heart conditions, particularly angina, but became increasingly popular due to other effects. Depending on expectancies of poppers use in individuals and the context in which these are used, effects may include mild euphoria and a heightened state of sexual arousal , as well as relaxant effects on certain muscles including the sphincter and vagina . Poppers are most commonly used before or during sexual activity but have always been used outside of sexual contexts, and an increase in non‐sexual recreational use among young people has been registered in different jurisdictions .…”
Section: Introductionmentioning
confidence: 99%
“…condomless anal intercourse (CAI) and multiple sexual partnerships (Carey et al, 2009;Hambrick et al, 2018;Sewell et al, 2017). Additionally, a systematic review of different substances used in nightlife settings ("club drugs") documented their associations with STI incidence (Drumright et al, 2006).…”
mentioning
confidence: 99%